2018
DOI: 10.1097/md.0000000000010759
|View full text |Cite
|
Sign up to set email alerts
|

The predictive value and the correlation of peripheral absolute monocyte count, tumor-associated macrophage and microvessel density in patients with colon cancer

Abstract: The tumor microenvironment plays a pivotal role in cancer progression. The purpose of the present study was designed to evaluate the predictive value of peripheral absolute monocyte count, tumor-associated macrophage, microvessel density, and to clarify the correlation between them in patients with colon cancer.A series of 216 patients with colon cancer were enrolled in this study. The peripheral absolute monocyte count was obtained from preoperative routine blood test. Tumor-associated macrophage and microves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
1
15
1
Order By: Relevance
“…CD68 is a generic macrophage marker, whereas CD163 and CD206 are believed to be markers more specific to M2 tumour associated macrophages that have been associated with a worse outcome [171]. There were twenty-two studies overall in colon or colorectal cancer although one study had an overlapping population [172], leaving twenty-one independent studies comprising 4879 patients [60,83,85,87,89,91,96,111,122,123,168,171,[173][174][175][176][177][178][179][180][181]. Of these, eleven studies (2038 patients) found that higher infiltration of macrophages were associated with a better prognosis [60,83,87,96,122,[175][176][177][178]180,181], compared with five studies (1965 patients) finding a worse prognosis [85,168,171,173,179].…”
Section: Macrophagesmentioning
confidence: 99%
See 3 more Smart Citations
“…CD68 is a generic macrophage marker, whereas CD163 and CD206 are believed to be markers more specific to M2 tumour associated macrophages that have been associated with a worse outcome [171]. There were twenty-two studies overall in colon or colorectal cancer although one study had an overlapping population [172], leaving twenty-one independent studies comprising 4879 patients [60,83,85,87,89,91,96,111,122,123,168,171,[173][174][175][176][177][178][179][180][181]. Of these, eleven studies (2038 patients) found that higher infiltration of macrophages were associated with a better prognosis [60,83,87,96,122,[175][176][177][178]180,181], compared with five studies (1965 patients) finding a worse prognosis [85,168,171,173,179].…”
Section: Macrophagesmentioning
confidence: 99%
“…Sixteen independent studies (3528 patients) assessed CD68 in colorectal cancer: of which ten (1998 patients) were associated with an improved outcome [60,83,87,96,122,175,177,178,180,181], one (654 patients) was associated with a worse outcome [85] and five (876 patients) found no difference [89,91,111,123,174]. The study that found a negative impact of CD68 on survival measured it in the IE compartment and ST compartment, finding that the presence of CD68 in the IE compartment impacted negatively on survival, whereas CD68 in the ST compartment made no difference to survival [85].…”
Section: Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these factors are probably associated not only with the outcomes of TAS-102 therapy but with CRC prognosis in general. For example, lower monocyte count is associated with better prognosis of localized CRC and metastatic disease [8][9][10][11] and was also con rmed as positive prognostic factor for TAS-102 in a study published by Kwakman and collaborators [7]. Similarly, elevated CRP levels are associated with poor prognosis of non-metastatic and metastatic CRC [12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 92%